Mechanical characterization of decayed wood in the field by ultrasound and static bending tests - Stangerlin, Diego Martins; Corassa, Janaína De Nadai; Gatto, Darci Alberto; Pereira, Roberto Lessa; Castelo, Patrícia Aparecida Rigatto (Comunicata Scientiae, 2015)
This study aimed to evaluate the natural resistance of four wood species exposed to field tests using ultrasound and static bending tests. Tectona grandis (teak), Azadaractina indica (neem), Inga sp. (inga) and Bagassa guianensis (tatajuba) logs with 1.2m length were subjected to field tests for 18 months, in the city of Sinop-MT. Samples were cut from healthy logs to characterize modulus of elasticity and modulus of rupture at static bending before the exposure in field test. After each period of exposure, samples were cut from the logs in three positions (in-ground contact, critical zone and above-ground). Nondestructive tests were performed using an ultrasound to determine the velocity of wave propagation in the decayed samples. Samples with lower velocities of wave propagation were subjected to the static bending tests. The results were compared with unexposed wood samples to characterize the degree of wood deterioration. Ultrasonic tests showed that samples collected from the critical zone of the logs presented lowest velocity of wave propagation. Among the species studied, teak and tatajuba wood presented the highest and the lowest natural resistance, respectively.